1999
DOI: 10.1080/14622299050011141
|View full text |Cite
|
Sign up to set email alerts
|

Smoking after nicotine deprivation enhances cognitive performance and decreases tobacco craving in drug abusers

Abstract: This study investigated the effects of nicotine deprivation and smoking on cognitive abilities and tobacco craving. Twenty smokers with histories of drug abuse completed the Questionnaire on Smoking Urges (QSU) and two cognitive tests before and after smoking two cigarettes during two 90-min sessions. After two cigarettes were smoked at Session 1, subjects were tobacco abstinent for 18 h until Session 2 the next morning. Response time on a logical reasoning test was unchanged by tobacco deprivation and was fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 41 publications
4
80
1
2
Order By: Relevance
“…The insensitivity of the Logical Reasoning Task to smoking history and acute challenge to nicotine conflicts with previous reports of abstinence-induced performance decrements and subsequent improvement after nicotine gum , or smoking (Bell et al 1999). In the latter study, although performance did not differ between a nonabstinent state and 18-h abstinence, the smoking of two cigarettes after abstinence reduced reaction time.…”
Section: Discusssioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The insensitivity of the Logical Reasoning Task to smoking history and acute challenge to nicotine conflicts with previous reports of abstinence-induced performance decrements and subsequent improvement after nicotine gum , or smoking (Bell et al 1999). In the latter study, although performance did not differ between a nonabstinent state and 18-h abstinence, the smoking of two cigarettes after abstinence reduced reaction time.…”
Section: Discusssioncontrasting
confidence: 77%
“…In nicotine-dependent individuals, tobacco deprivation can impair attentional and cognitive abilities within 12 h of smoking cessation (Bell et al 1999;Gross et al 1993;Lyvers et al 1994), and nicotine administration or cigarette smoking can reverse such deficits to predeprivation performance levels (Bell et al 1999;Parrott and Roberts 1991). Whether improved performance associated with relief from withdrawal should be considered cognitive enhancement has been questioned (Heishman et al 1994;Hughes 1991).…”
mentioning
confidence: 99%
“…Nicotine administration also has been reported to improve reaction time (regardless of smoking status) as well (Ernst et al, 2001a). Consistent with these findings are studies which demonstrate that acute abstinence from smoking (within 12 h) results in slowed response times (Bell et al, 1999;Gross et al, 1993;Thompson et al, 2002).…”
Section: Effect Of Nicotine On Brain Activation During Cognitive Tasksmentioning
confidence: 53%
“…Smokers commonly believe that smoking improves attention, alertness and concentration (West, 1993) and such perceived benefits have been suggested to motivate continued smoking (Heishman et al 2010). A plethora of studies have demonstrated that smoking can improve, and deprivation impair, performance on a variety of cognitive domains including reaction time (Bates et al 1995;Giannakoulas et al 2003;Perkins et al 1995), vigilance/attention (Bell et al 1999;Gilbert et al 1997), inhibitory control (Powell et al 2001), learning (Soar et al 2008), and working memory (Jacobsen et al 2005;Merritt et al 2012). Nicotine replacement therapy (NRT) is also associated with attenuation of tobacco withdrawal symptoms (Kleykamp et al 2008;Shiffman et al 2006) and improved cognitive performance in abstinent smokers.…”
Section: Introductionmentioning
confidence: 99%